2021
DOI: 10.1371/journal.pbio.3001498
|View full text |Cite
|
Sign up to set email alerts
|

The human gut symbiont Ruminococcus gnavus shows specificity to blood group A antigen during mucin glycan foraging: Implication for niche colonisation in the gastrointestinal tract

Abstract: The human gut symbiont Ruminococcus gnavus displays strain-specific repertoires of glycoside hydrolases (GHs) contributing to its spatial location in the gut. Sequence similarity network analysis identified strain-specific differences in blood-group endo-β-1,4-galactosidase belonging to the GH98 family. We determined the substrate and linkage specificities of GH98 from R. gnavus ATCC 29149, RgGH98, against a range of defined oligosaccharides and glycoconjugates including mucin. We showed by HPAEC-PAD and LC-FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…It does not mean that these associations do not exist, but they may be obscured by the large diversity of the human gut microbiota and by the possibility that FUT2 or HBGAs influences take place at the strain level rather than at the genus or species levels. Thus, a human gut symbiont, Ruminococcus gravis was recently reported to display a strain-specific repertoire of glycosidases, one of them showing specificity for a blood group A tetrasaccharide (Wu et al, 2021). Microbiota composition could also be affected by the strain-specific display of HBGA-specific bacterial adhesins such as the blood group A and B-specific adhesin of a Lactobacillus mucosae strain (Watanabe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not mean that these associations do not exist, but they may be obscured by the large diversity of the human gut microbiota and by the possibility that FUT2 or HBGAs influences take place at the strain level rather than at the genus or species levels. Thus, a human gut symbiont, Ruminococcus gravis was recently reported to display a strain-specific repertoire of glycosidases, one of them showing specificity for a blood group A tetrasaccharide (Wu et al, 2021). Microbiota composition could also be affected by the strain-specific display of HBGA-specific bacterial adhesins such as the blood group A and B-specific adhesin of a Lactobacillus mucosae strain (Watanabe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, associations with the microbiota composition and FUT2 polymorphisms have been reported (Rausch et al, 2011;Wacklin et al, 2011;Tong et al, 2014;Wacklin et al, 2014;Gampa et al, 2017;Kumbhare et al, 2017;Rodríguez-Díaz et al, 2017;Pan et al, 2021;Rühlemann et al, 2021;Lopera-Maya et al, 2022). Although these remain debated and not fully consistent across studies (Davenport et al, 2016;Turpin et al, 2018), there are strong indications that microbiota composition is partly dependent on gut mucosal glycan composition through either bacterial adhesion molecules or through bacterial use of fucosylated glycans as nutrients (Coyne et al, 2005;Watanabe et al, 2010;Kashyap et al, 2013;Pickard et al, 2014;Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The genus of Fusobacterium in the gut microbiome is often associated with meat digestion as reported in other predators ( Ley et al, 2008 ; Keenan et al, 2013 ; Nelson et al, 2013 ; Nishida and Ochman, 2018 ). Ruminococcus gnavus , an early colonizer of the human gut ( Kelly, 2016 ; Wu et al, 2021 ), was reported to be associated with mucin glycan utilization, which is important for the colonization of bacteria in the gut ( Tailford et al, 2015 ; Lim et al, 2017 ). Species of Bacteroides are important for metabolizing polysaccharides and oligosaccharides, which could provide nutrition and vitamins to the host and other intestinal microbial residents ( Wexler, 2007 ; Zafar and Saier, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes from several GH families have been demonstrated to contribute to host-glycan Mann et al, 6 breakdown (27,41,(48)(49)(50)(51), and new N-and O-glycan-targeting enzymes are being actively reported (52)(53)(54)(55). Together, these factors hinder bioinformatic annotation of a given GH's macromolecular target and a microbe's carbohydrate preferences.…”
Section: Mann Et Almentioning
confidence: 99%
“…Critically, the mucous layer is often thinner during inflammation, and bacteria encroach towards the epithelial surface where they are better positioned to induce an immune response (24,25), akin to mice with genetically compromised mucous barriers. breakdown (27,41,(48)(49)(50)(51), and new N-and O-glycan-targeting enzymes are being actively reported (52)(53)(54)(55). Together, these factors hinder bioinformatic annotation of a given GH's macromolecular target and a microbe's carbohydrate preferences.…”
Section: Introductionmentioning
confidence: 99%